2014
DOI: 10.1016/j.ejmech.2014.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal activity and DNA binding of N-substituted N-phenylbenzamide and 1,3-diphenylurea bisguanidines

Abstract: The compounds were tested against T. b. rhodesiense and P. falciparum.N-alkylated compounds 7b and 7c were 100% curative in the STIB900 mouse model of HAT.DNA binding affinity was measured by SPR with AATT, (AT) 4 and (CG) 4 hairpin duplexes.7b and 7c bind selectively to AT-rich DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…3,4,7 In previous studies, we have discovered diphenyl dicationic compounds 1-5 (Chart 1) that showed excellent in vivo activity against African trypanosomes (T. b. rhodesiense) in mouse models of sleeping sickness. [9][10][11][12] The binding interaction of 5 with the minor groove of the all-AT DNA sequence dIJAAAATTTT) 2 and with the selfcomplimentary nucleotide dIJCTTAATTCGAATTAAG) 2 was demonstrated by X-ray crystallography. 13,14 Nagle et al showed that arylamide derivatives 1 and 2 bound strongly and selectively to AT oligonucleotides with a slight preference (2-to 3-fold) for dsDNA CGAATTCG vs. CATATATAT sequences.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,7 In previous studies, we have discovered diphenyl dicationic compounds 1-5 (Chart 1) that showed excellent in vivo activity against African trypanosomes (T. b. rhodesiense) in mouse models of sleeping sickness. [9][10][11][12] The binding interaction of 5 with the minor groove of the all-AT DNA sequence dIJAAAATTTT) 2 and with the selfcomplimentary nucleotide dIJCTTAATTCGAATTAAG) 2 was demonstrated by X-ray crystallography. 13,14 Nagle et al showed that arylamide derivatives 1 and 2 bound strongly and selectively to AT oligonucleotides with a slight preference (2-to 3-fold) for dsDNA CGAATTCG vs. CATATATAT sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mode of action of the antitrypanosomal lead compounds I to V, earlier studies have shown that this class of dicationic compounds binds to the DNA minor groove at AT-rich sequences (55)(56)(57)(58). In trypanosomes, the kinetoplast DNA (kDNA) has a high content of AT-rich regions that could be a site of selective action of this kind of compound (59).…”
Section: Discussionmentioning
confidence: 99%
“…For the antiprotozoal and antimicrobial properties of phenylbenzamides, see: Ríos Martínez et al (2014); Ş ener et al (2000). For active metabolites of benzoxazoles, see: Mobinikhaledi et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…The crystal structure determination of the title compound (I), is part of a study on phenylbenzamides carried out in our research group, and they are synthesized from the reaction of picryl benzoates with 2-hydroxy-aniline. These compounds have received extensive attention because of their antiprotozoal (Ríos Martínez et al, 2014) and anti-microbialactivity (Şener et al, 2000), and as active metabolites of benzoxazoles (Mobinikhaledi et al, 2006). They have also been studied as inhibitors of tyrosine kinases (Capdeville et al, 2002) and inducers of apoptosis in the tumor development process (Olsson et al, 2002).…”
Section: S1 Commentmentioning
confidence: 99%